Local industry in global networks : changing competitiveness, corporate strategies and pathways of development in Singapore and Malaysia's garment industry - Smakman, Floortje (My University, 2004)
The garment industry in Singapore and Malaysia has been incorporated into global production networks and commodity chains - driven by large US and European garment companies - since the 1960s and 1970s respectively. The industry was an intricate part of the export led industrialisation strategies adopted by both countries. However, since incorporation, changing competitiveness due to both international, regional end local pressures, has meant local garment firms have had to implement a range of adjustment strategies in order to survive and ideally improve their competitive positioning. An in-depth empirical study of these strategies and their outcomes forms the core of this study. Considering corporate strategies and identifying the most common development trajectories as well as the factors behind them, allows for an analysis of the longer-term opportunities that operating in global networks and chains offers. More importantly it gives an insight into whether and how these opportunities are indeed leveraged for local firm and industry development. The study illustrates the complexity of these issues and the importance of not just global, but particularly local dynamics for positive local firm and industry development. As such it contributes to one of the central issues in the current globalisation debate: How firms and industries in less developed countries may gain from globalisation.
Keywords: Aardwetenschappen; global networks; local industry; firm strategies; development trajectories; garment industry; Singapore; Malaysia